Pengembangan Media Pembelajaran Vitual Laboratory Berbasis Android Untuk Meningkatan Kemampuan Berpikir Kritis Dan Pemecahan Masalah - Mustikasari, Ane; Hindriana, Anna Fitri; Arif, Asep Ginanjar (Program Studi Pendidikan Biologi, Sekolah Pascasarjana Universitas Kuningan, 2021)
The development of technology and information in the world of education is very fast but its utilization is not optimal in the learning process. Therefore it is necessary to develop learning media by utilizing technological developments to assist the learning process such as practicum activities because the facilities for carrying out conventional practicums are not adequate, so that the existence of technology can facilitate these limitations. This research method is Research and Development which adapts the ADDIE development model, the research subjects are class XI students of SMAN 1 Taraju, Tasikmalaya Regency. This learning media is said to be very feasible based on due diligence according to media experts with a total percentage of 98%, material experts with a total percentage of 93.63%. This learning media in its application is able to improve critical thinking skills and problem solving 0.75 in the high category, namely with an average normalized N-gain index from pretest to posttest of 0.97 in the high category while the results of student responses to learning media with a total percentage of 94 % with very strong category. Based on the results of the study it can be concluded that the development of Android-based Virtual Laboratory learning media can improve critical thinking skills and problem solving.